Advanced Techniques and Antenna Design for Pulse Shaping in UWB Cognitive Radio - Lise Safatly; Mohammed Al-Husseini; Ali El-Hajj; Karim Y. Kabalan (International Journal of Antennas and Propagation)
Spectrum scarcity has emerged as a primary problem in the communications technology. The combination of cognitive radio (CR) and ultra-wideband impulse radio (UWB-IR) has been proposed to solve the shortage problem by allowing smart and adaptive spectrum management, leading to UWB-CR. In a UWB-CR scheme, secondary users are supposed to ensure interference avoidance by adaptively selecting the portions of the spectrum not being used by primary users. In this paper, three different techniques for the generation of adaptive UWB pulses are studied. The Parks-McClellan algorithm is employed, a neural network is trained, and a reconfigurable band stop filter is designed to generate an adaptive waveform with nulls at specific frequencies. Simulations, measurements, and analysis show that each generated UWB pulse has remarkable advantages in the frequency utilization, spectrum avoidance, and hardware implementation.